Characteristics of Scots pine (Pinus sylvestris L.) seeds from seed orchards of different ages in the State Enterprise “Klavdiievo Forest Research Station” - Шлончак, Г. А.; Ящук, І. В.; Митроченко, В. В.; Лавренюк, О. А. (Forestry and Forest Melioration, 2024)
Introduction The most effective method for establishing seed orchards is by planting grafted, containerised seedlings. Seed orchards focused on cultivating plus trees of Scots pine in the Staropetrivske and Pershotravneve Forestries in the Klavdiievo Forest Research Station were first established in 1976 using this approach. The initial “flowering” of clone plantations was observed in the same year as grafting. By the third year after grafting, 15–25% of trees had already begun producing generative organs. By the age of 10, all clones were “flowering” and yielding seeds, with an average seed production of 2–5 kg per ha. The operational lifespan of forest seed orchards is relatively short – 25 to 30 years – provided they receive annual maintenance. In our study, 25-year-old orchard trees reached an average height of 11.3 m, making it impossible to harvest cones from the ground. Even with ladders and hooks, only 17.7% of cones could be collected. This research aimed to assess the relationship between Scots pine cone and seed characteristics and plantation age, as well as the feasibility of using seeds from older plantations for reforestation. Materials and Methods The study was conducted across 11 seed orchards of Scots pine (clonal, family, and family-clonal), ranging from 12 to 47 years old, within the Staropetrivske and Pershotravneve Forestries under the State Enterprise “Klavdiievo Forest Research Station”. The planting patterns of seed trees varied, including 5 x 5 m, 5 x 10 m, 10 x10 m, and 7 x 7 m configurations. For each orchard, data were collected on 20 trees, including total height, height to the first live branch, crown length, and crown projection. During the winter of 2022–2023, research station specialists collected up to 60 cones from each of 11 seed orchards to assess the quality of genetically improved Scots pine seeds. As a control, cones of the bulk collection from a 73-year-old Scots pine plantation in compartment 109 of Staropetrivske Forestry were used. Cone morphological characteristics were analysed according to L.F. Pravdin’s method, while seed characteristics were determined using V.A. Cherepnin’s scale. Seed mass and sowing properties (germination and vitality) were assessed according to the Ukrainian State Standard DSTU 8558:2015. Results Quality indicators showed that cones from all seed orchards exceed those from the bulk collection. Cone size correlated with mass, with the heaviest cones (15.7 g) observed in the family-clonal plantation (KNP-2010). Cones from four plantations contained over 30 seeds each, compared to 12.8 seeds in the control sample. The yield of filled seeds ranged between 0.46–1.97%. The seeds from all plantations, including those from the control plot, were classified as medium-sized (6.0–8.6 g). Germination tests under laboratory conditions showed that seed germination energy on the seventh day was 86–100%, with final germination rates of 96–100%. Conclusions Cones and seeds from all studied seed orchards outperformed the control (bulk collection) in terms of quality. All seeds had a high quality, and their germination rates remained consistently high (96–100%), indicating that seeds from seed orchards, regardless of plantation age, should be prioritized for producing planting material for reforestation efforts. 5 Tables, 25 Refs.